Analisis Pemanfaatan Google Maps sebagai Fungsi Promosi dan Media EWOM pada Tempat Usaha Kuliner - Rizqiawan, Hendrik; Novianto, Iful; Permana, Galuh Argo; Wahyudi, Aris Candra (Journal of Trends Economics and Accounting Research, 2025)
This research was conducted with a quantitative approach using primary data from the distribution of questionnaires to 97 respondents. The purpose of this study is to test and analyze the extent to which Google Maps can function as an effective promotional tool and EWOM media, which has an impact on visitor decisions at culinary business locations / places in Surabaya, especially for potential customers who will visit for the first time or customers who have rarely come. The regression analysis results show that the significance values for the independent variables, which include menu features (food and beverages) and photo and video features that act as promotional functions or tools, and review and rating features that represent EWOM media, are 0.019, 0.007, and 0.030 respectively on the dependent variable of visiting decisions. This shows that the menu (food and beverage) feature variables, photo and video features, and review and rating features have a significant influence on visitor decisions to culinary business locations/places in Surabaya City. This research proves that Google Maps is worth considering as a function or promotional tool and effective EWOM media, especially by culinary business managers in Surabaya.